Análise do processo de gestão do conhecimento em uma indústria metal-mecânica: diferenças entre os níveis tático e operacional - Colombelli, Gilmar Luiz (2007)
The development, the education and the capacity of learning become indispensable to employability of people, to organizations and to society, considering the present context increasingly dynamic, interdependent and unexpected, marked by only one certainty, a permanent change. The main focus of this dissertation is to analyze how the processes which relate to the management of knowledge happen in a metal-mechanical industry, in the vision of the components of the tactical and operational level of the metal-mechanical sector, situated in the central region of the state of Rio Grande do Sul. The theoretical presuppositions which have given basis to this dissertation have dealt with the relation between the management of knowledge and the organizational environment, regarding as focus the model of Spiral of Knowledge (Nonaka and Takeuchi, 1997) which worries about the ways of conversion of knowledge and the process of learning, fruit of social interactions which establish in the work environment. In order to implement the present research one has adopted a qualitative method, developed in a study of simple case of an exploratory type. The data have been collected through semistructured individual interviews with managers, and workers of operational level of the metal-mechanical industry, object focus of this study, and documental sources. To the systematization and interpretation of data, an analysis of content has been adopted, trying to understand the theme of research from the speech of the participants. The results of the research evidence that the contacts and the interrelationships between people constitute a key factor which allows the process of learning in the individual, organizational and group levels. These premises are put into effect by the company, where it is possible to affirm that the tactical level of the company differs from the operational level in what concerns the processes of dissemination of new knowledge. In the variables externalization, combination, internalization and management of knowledge, it is visible the greater participation of it, having only in the process of socialization of new knowledge a balance between the tactical and operational levels. One also characterizes that the informal processes are more effective in the company than the formal processes of dissemination of new knowledge. The study points out to the necessity of recognizing explicitly that the organization has a fundamental role in the process of creation of its knowledge, facilitating the accomplishment of group activities, in a way that permits the recreation and the storing of individual knowledge because the processes of creation of organizational knowledge happen with the action of supporting the creative individual and to cultivate an adequate environment to its creation